Superficiary right of building: Origin and development in Central Europe - Pavel Petr (DANUBE: Law, Economics and Social Issues Review, 2016)
The Czech Republic has been dealing for the last four years with a legal revolution in the field of private law. A new Civil Code was adopted in 2012 and many new and forgotten legal figures were restored in the text of the code. An interesting example of forgotten legal figures is the superficiary right of building, which has again entered the legal order of the Czech Republic after a long one hundred years. Unlike the Act on the Superficiary Right of Building of 1912, the new Civil Code extends the scope of persons that may create the superficiary right of building to their land. This should eliminate the obstacle that has substantially limited its wider use. The superficiary right of building is not likely to become a legal concept very frequently seen in public registers. The aim of this paper is, therefore, a reflection on divided ownership and the purpose and genesis of the superficiary right of building in relation to its origins, as well as a prediction of future developments of this legal concept in the real estate market. To analyse the concept, the paper employs formal and legal methods (logical, grammatical and historical method). A comparative study is conducted in the spirit of the comparative method. The superficiary right of building is a suitable complement to the range of options of property rights offered by the new Civil Code. The author concludes that the use of the superficiary right of building, although not limited in comparison with the 1912 Act, will likely be less frequent and focused on longer-term projects.
Keywords: 330; Superficiary Right of Building; Divided Ownership; Superficies Solo Cedit; Private Law